2008
DOI: 10.2478/v10009-008-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Holocene diatom biostratigraphy of the SW Gulf of Gdańsk, Southern Baltic Sea (part III)

Abstract: The palaeoenvironmental changes of the south-western part of the Gulf of Gdańsk during the last 8,000 years, with reference to the stages of the Baltic Sea, were reconstructed. Diatom analyses of two cores taken from the shallower and deeper parts of the basin enabled the conclusion to be drawn that the microflora studied developed in the three Baltic phases: Mastogloia, Littorina and Post-Littorina. Moreover, the so-called anthropogenic assemblage was observed in subbottom sediments of the study area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…These species were noted as abundant in the previous studies on the Post-Littorina flora of the Gulf of Gdańsk (Witkowski 1994 The so-called 'anthropogenic assemblages' of diatoms were identified in the upper parts of cores R11, R12 and R13. The thickness of the zones varied from 14 cm in R12 and R13 to 23 cm in R11, which is comparable with the previous diatom analysis of bottom sediments of the study area (Witkowski 1994, Witkowski & Pempkowiak 1995, Stachura-Suchoples 1999, Leśniewska & Witak 2008, Witak 2010). Thickness differences between R11-II, R-12-II and R13-II DAZ may be explained by different sedimentation rates within the gulf.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These species were noted as abundant in the previous studies on the Post-Littorina flora of the Gulf of Gdańsk (Witkowski 1994 The so-called 'anthropogenic assemblages' of diatoms were identified in the upper parts of cores R11, R12 and R13. The thickness of the zones varied from 14 cm in R12 and R13 to 23 cm in R11, which is comparable with the previous diatom analysis of bottom sediments of the study area (Witkowski 1994, Witkowski & Pempkowiak 1995, Stachura-Suchoples 1999, Leśniewska & Witak 2008, Witak 2010). Thickness differences between R11-II, R-12-II and R13-II DAZ may be explained by different sedimentation rates within the gulf.…”
Section: Discussionsupporting
confidence: 89%
“…It is known as a eutraphentic taxon tolerating α-mesosaprobic environment (van Dam et al 1994, Stachura-Suchoples 2001. In the study area it was observed by Witkowski (1994), Witkowski & Pempkowiak (1995), Stachura & Witkowski (1997), Stachura (1999), Witak (2000), , Leśniewska & Witak (2008) and Witak (2010). This species was recorded also in the Gulf of Finland (Weckström et al 2004, Clarke et al 2006) and the Gulf of Riga (Olli et al 2008) and the Szczecin Lagoon (Bąk et al 2001).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations